Assessment of surgical patients’ knowledge about anaesthesia and anaesthesiologist in a tertiary care teaching institute-a survey - Marulasiddappa, Vinay; H. N., Nethra (International Journal of Research in Medical Sciences, 2018)
Background: Anaesthesia is a speciality, playing a crucial role in the perioperative care of patients. Complex surgeries are facilitated due to the anaesthesiologists catering to the ever-advancing surgical field requirements. Although an important speciality, patients are unaware of the speciality of anaesthesia and anaesthesiologist. Patients are subjecting themselves for surgical procedures without having adequate knowledge of anaesthesia and anaesthesiologist. Hence, the survey was designed with the aim to assess the patients’ knowledge about anaesthesia and anaesthesiologist in surgical patients. Methods: A cross sectional study conducted on four hundred surgical inpatients using predesigned questionnaire containing questions related to the knowledge of anaesthesia and anaesthesiologist. The results were expressed as percentages. Chi-square/ Fisher Exact test was used to find the significance of study parameters. Results: Anaesthesiologists were considered as “doctors” by 60.5% of patients; Thirty three percent of the survey population had “no idea” of Anaesthesia. The survey populations’ knowledge about complications was 32.25%. Awareness about separate consent for anaesthesia was 49%. Anaesthesiologists’ work place was not known to 77.5% of survey population. Anaesthesiologists’ role in operation theatre was known only in 59.5% and remaining 40.5% were unaware of Anaesthesiologists’ role. None of the patients preferred to meet the Anaesthesiologists before surgery. Conclusions: Surgical inpatients in tertiary care hospital have a poor understanding of anaesthesia and poor recognition of the role of anaesthesiologist. The knowledge about anaesthesia and anaesthesiologist is not known in general population. Hence, anaesthesiologists must work towards getting recognition for the speciality of anaesthesiology and the anaesthesiologists.